Binaural sound reproduction in car compartments - A feasibility study using four channels - Karlberg, Jonas (My University, 2017)
Binaural audio material can be presented with the use of headphones or a set of loudspeakers. When using the latter, the playback system should compensate for the occurring crosstalk which is done with the use of crosstalk cancellation filters. A car compartment is considered to be acoustically challenging, for spatial reproduction over loudspeakers, due to the many reflecting surfaces. The thesis set out to investigate suitable loudspeaker positions that might be in favour for a rougher estimation of the cancellation filters, making the system more robust. Another aim was to find a method for filter design. Firstly, a test rig with two loudspeakers was set up to try different loudspeaker positions. When the positions were set, the filters were tuned and tested with the test rig as well as inside a car compartment. Two separate systems were implemented, one behind and one in front of the listener, referred to as back and front system. When the tuning process was completed three user studies were conducted using three different loudspeaker setups: one setup using four similar loudspeakers placed in a listening room, one setup with custom built loudspeakers implemented in a car compartment and the final setup placed inside the listening room using the custom built loudspeakers from the car. The participants were asked to localise virtual source positions generated by either the back or front system. An instrumental evaluation was performed by testing the created filters in a virtual system. Head shadowing and crosstalk performance were studied. Furthermore, a method of filter design was developed along with a measurement script for use with Matlab or Octave. Two of the main findings from the user study are: • The back system was suitable for presenting virtual source positions behind the listener. For source positions in front of the listener most answers resulted in front/back confusions. These tendencies were shown for all tests. • The front system was found to have a more uniform representation of source positions for the tests performed in the listening room. The system inside the car would need further tuning to increase system performance. Keywords: binaural reproduction, 3D sound, filter design, car HMI, signal processing
Keywords: Building Futures; Akustik; Building Futures; Acoustics